A Technical Overview of XBRL. - Pandrangi, Srinivas (XML journal :the ultimate enterprise resource.)
This article provides a technical overview of the XBRL standard, with emphasis on the architecture of the standard and the potential applications surrounding the business reporting functionality it supports.